2015
DOI: 10.1016/j.cej.2014.07.138
|View full text |Cite
|
Sign up to set email alerts
|

Producing free nitrous acid – A green and renewable biocidal agent – From anaerobic digester liquor

Abstract: Recent studies have shown that free nitrous acid (FNA) at parts per million is strongly biocidal to a broad range of microorganisms involved in wastewater management. Applications have been developed, where FNA is used to deactivate anaerobic sewer biofilms thus suppressing sulfide and methane production in sewers, or to lyse secondary sludge resulting in reduced sludge production and enhanced biogas production. This study examines the feasibility of producing FNA from a waste stream namely the anaerobic sludg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 34 publications
(39 reference statements)
0
60
0
Order By: Relevance
“…Free Nitrous Acid (FNA) has been demonstrated to be very effective in improving biomethane produced from digester liquor through complete conversion of ammonium to nitrite with alkalinity addition in a partial nitrification reactor (Law et al, 2015;Wang et al, 2014b). However when a source of nitrite is not available in wastewater treatment plants (WWTPs), this pre-treatment can become expensive due to the costs associated with the purchase of commercial nitrite and hydrochloric acid to achieve high FNA concentrations (Zahedi et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Free Nitrous Acid (FNA) has been demonstrated to be very effective in improving biomethane produced from digester liquor through complete conversion of ammonium to nitrite with alkalinity addition in a partial nitrification reactor (Law et al, 2015;Wang et al, 2014b). However when a source of nitrite is not available in wastewater treatment plants (WWTPs), this pre-treatment can become expensive due to the costs associated with the purchase of commercial nitrite and hydrochloric acid to achieve high FNA concentrations (Zahedi et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The first one took into consideration the fact that FNA can be produced on site. Previous study demonstrates that FNA can be produced in-situ as a by-product of wastewater treatment on site in a WWTP using anaerobic digestion liquor (Law et al, 2015). The ammonium (~ 1 g N/L) in the anaerobic digestion liquor can be converted into nitrite through partial nitritation resulting in a nitrite concentration of up to 1 g N/L at pH ~6, equivalent to an FNA concentration in the order of ppm level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that both FNA and H 2 O 2 can be produced as by-products of wastewater treatment through partial nitritation of anaerobic digestion liquor, with low chemical and energy input , Law et al, 2015, and through a bio-electrochemical system (Rozendal et al, 2009), respectively. In order to assess the potential economic feasibility of the proposed combined pre-treatment at full-scale, a desktop scaled-up study on a full-scale WWTP with a population equivalent (PE) of 400,000 and an anaerobic sludge digester with a hydraulic retention time (HRT) of 20 days was performed (Table 10).…”
Section: Combination Of Fna and Oxidants As A Potential Pre-treatmentmentioning
confidence: 99%
See 2 more Smart Citations